Factors of breastfeeding discontinuation among working mothers in UiTM Selangor Puncak Alam Campus/ Imliya Ibrahim and Syahrul Bariah Abdul Hamid - Ibrahim, Imliya; Abdul Hamid, Syahrul Bariah (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Breastfeeding provides optimum health outcomes in short and long-term among children and mothers. Maternal return to work reported as the main obstacle for breastfeeding continuation especially in Selangor that had higher rate of labour force participation among women. Our study aimed to determine the prevalence of breastfeeding practice and investigate the predictors of breastfeeding discontinuation among employed mothers. 45 working mothers with children aged below two years were recruited using purposive sampling in this cross sectional study. Iowa Infant Feeding Attitude Score were used to assess maternal attitude towards breastfeeding. Out of 45 respondents, 28.9% discontinued breastfeeding, meanwhile 46.2 % had breastfed their babies for more than six months and 50.0 % continued breastfeeding at two years old. Early breastfeeding initiation rate was 60.0%. Exclusive breastfeeding rates were 22.5%, 12.5% and 65.0% at 2 months, 3 to 5 months and more than 6 months respectively. Majority of mothers (66.7%) introduced complementary food as recommended. Breastfeeding discontinuation was associated with the level of knowledge, breastfeeding attitudes and employer support (p< 0.05). Further analysis revealed the odds of breastfeeding discontinuation were higher for women with low attitude towards breastfeeding and did not receive employer support. Therefore, it is important to improve workplace settings into breastfeeding-friendly for mothers to continue to breastfeed their infants while still working.